Quantitative determination, principal component analysis and discriminant analysis of eight marker compounds in crude and sweated Dipsaci Radix by HPLC-DAD - Weifeng Du; Xiaoning Li; Ying Yang; Xianke Yue; Dongjing Jiang; Weihong Ge; Baochang Cai (Taylor & Francis Group, 2017)
Context: Dipsaci Radix is derived from the dry root of Dipsacus asper Wall.ex Henry (Dipsacaceae). It has attracted increasing attention as one of the most popular and precious herbal medicines in clinical use. Objective: To develop a HPLC-DAD method for quantitative analysis and quality control of eight active components in crude and sweated Dipsaci Radix. Materials and methods: The eight components in Dipsaci Radix were analyzed by HPLC-DAD on an Agilent Eclipse XDB-C18 column within a gradient elution of acetonitrile and 0.05% formic acid aqueous solution. ESI-MS spectra were acquired on a triple quadrupole mass spectrometer. Validation was performed in order to demonstrate linearity, precision, repeatability, stability, and accuracy of the method. The results were processed with principal component analysis (PCA) and discriminant analysis (DA). Results: The eight components showed good linearity (R2 > 0.9991) in the ranges of 60.40-1208.00, 151.00-3020.00, 3.06-61.20, 30.76-615.20, 5.13-102.60, 10.17-203.40, 10.20-204.00, and 151.60-3032.00 mg/mL, respectively. The overall recoveries were in the range of 99.03-102.38%, with RSDs ranging from 1.89% to 4.05%. Through PCA, the degree of importance of the eight components in sequence was CA > AVI > IA > LA > LN > IC > IB > CaA. The crude and sweated Dipsaci Radix were distinguished obviously by DA. Discussion and conclusion: The method, using HPLC-DAD analysis in combination with PCA and DA, could provide a more comprehensive and quantitative chemical pattern recognition and quality evaluation to crude and sweated Dipsaci Radix.